Case Report: Sengers syndrome caused by a novel 7.6 kb AGK deletion misdiagnosed as isolated congenital cataract - Gong, Xingwang; Liu, Yue; Liang, Hui (Frontiers in Pediatrics, 2026)
The diagnosis of Sengers syndrome, a rare mitochondrial disorder, is often challenged by phenotypic mimicry. We report a diagnostically instructive case of a 4-month-old female who presented with the classic triad of congenital cataracts, hypertrophic cardiomyopathy, and lactic acidosis. Initial whole-exome sequencing (WES) was confounded by the finding of a heterozygous variant in CRYBA2 and only a single heterozygous nonsense mutation in AGK (c.409C>T, p.Arg137*). The persistence of a multisystemic phenotype inconsistent with an isolated cataract disorder prompted further investigation. Copy number variation (CNV) analysis of the WES data revealed a large heterozygous deletion in AGK, which breakpoint-specific polymerase chain reaction and Sanger sequencing precisely characterized as a novel 7.6 kb deletion (chr7:141297542-141305156). This confirmed compound heterozygosity, yielding a definitive diagnosis of Sengers syndrome and reclassifying the CRYBA2 variant as incidental. Crucially, breakpoint analysis indicated a non-Alu-mediated mechanism for the deletion. This case highlights the critical importance of CNV analysis in resolving genetically ambiguous autosomal recessive cases and provides novel insight into the structural mutational landscape of AGK.